Data encryption using chaotic mechanical system vibration response signal - Poa, Jeffry Ming Xiong (2019)
It is known that fractional derivatives are increasingly used due to the ability in describing memory effects and uncharacteristic behaviour which further combined with mechanical system to form chaos. These chaotic systems can be used to increase key spaces and hence reducing the potential risk of brute-force attacks. In this paper, an innovative algorithm for image encryption based on a chaotic mechanical system is proposed. The key idea of the paper is to come up with a chaotic system focusing on the properties of fractional derivatives on the second-order mechanical system. Subsequently, analysis of the chaotic system is conducted to ensure the suitability for image encryption. The algorithm used for encryption focus on combining the plain-image with the chaotic generated response by XOR. The proposed plain-image is successfully encrypted and decrypted with detailed analysis of the randomness and security of the encrypted image. The performance of the proposed algorithm was analysed, and satisfactory results were achieved.